Information and communication technology innovation as a tool for promoting sustainable agriculture: a case study of paddy farming in west Malaysia / Zakirah Othman - Othman, Zakirah (2012)

(untitled)
Sustainable agriculture refers to the farm’s ability to maintain production and giving benefits based on maintaining nature and the ecosystem indefinitely. Malaysia aims to transform current agricultural activities into advanced, innovative and sustainable practices. In the recently announced Third National Agricultural Policy, there are many issues highlighted to promote the sustainability of agricultural practices. However, this is not an easy task because there are basic problems that the farmers will encounter, especially with regards to their understanding of sustainable agriculture. As an alternative solution, introducing Information and Communication Technology (ICT) applications is a novel way to increase awareness and promote sustainable agriculture practices. In this context, Sustainable Paddy Farming System (SiPadi) is designed as a persuasive learning tool in virtual paddy farming to promote sustainable paddy farming among the young generation, especially among university students in Malaysia. Virtual reality technology and persuasive technology have been adapted in the design of the prototype. This study involved three phases. Phase 1 was undertaken to understand and identify sustainable paddy farming; Phase 2 attempted to develop an education prototype which acts as a tool to disseminate information about sustainable paddy farming. In other words, it means that the real life practices of sustainable paddy farming have been adapted in the design of the prototype. Lastly, Phase 3 involved the testing and evaluating of the prototype. This research employed a qualitative and quantitative research design. Data were collected through reviews of existing literature, interviews, observation and lab experiments. The location of the case study is paddy farming areas in selected areas in West Malaysia. The findings of this study produced two major outcomes: the identification of sustainable paddy farming; and the design strategies of the prototype. First, there are several similarities and differences in the practice of paddy farming in the locations of the case study. The paddy farming in Bandar Baru Tunjong, Kahang and Tanjung Karang can be categorised as sustainable. Second, the evaluation of SiPadi indicated that this prototype was successful in creating awareness among the respondents.